Generation of intense high harmonics: i) to test and improve resolution of accumulative x-ray streak camera ii) to study the effects of carrier envelope phase on XUV super continuum generation by polarization gating - Shakya, Mahendra Man (Kansas State University, 2007)
The first part of this thesis describes our novel design, test, and application of our X-ray streak camera to the pulse duration measurement of soft X-rays. We demonstrated a significant improvement in the resolution of the x-ray streak camera by reducing the electron beam size in the deflection plates. This was accomplished by adding a slit in front of the focusing lens and the deflection plates. The temporal resolution reached 280 fs when the slit width was 5 μm. The camera was operated in an accumulative mode and tested by using a 25 fs laser with 2 kHz repetition rate and 1-2% RMS pulse energy stability. We conclude that deflection aberrations, which limit the resolution of the camera, can be appreciably reduced by eliminating the wide-angle electrons. We also employed the same streak camera to demonstrate that it is capable of measuring the pulse duration of X-rays. We measured the pulse duration of X-rays emitted from Ni-like Ag and Cd grazing-incidence laser to be ~5ps. The measured value agrees with the prediction made by the model and the measurement made by changing the delay as a function of the pulse duration. The streak camera was also tested with various sources of X-ray such as high harmonics generation of soft x-rays from an argon atom using a high power Ti:sapphire laser source of KLS. The result of the measurement manifests its capability for serving as a detector in the study of ultrafast dynamics in the field of physics, chemistry, biology and medical sciences. The second part of this thesis describes our design of a spectrometer to study the effect of the Carrier envelope (CE) phase on polarization gated extreme-ultraviolet (XUV) super-continuum generation. Because the challenge of making single shot experiment possible is to generate a sufficient number of photons, our setup has been built to allow generation of high order harmonics at the maximum phase matched pressure. This is the first time to our knowledge that phase matching in the polarization gating process has been studied so far. We measured the maximum phase matching pressure to be ~ 55 Torr which is the pressure above which quadratic increase in intensity of the high harmonics spectrum ceases to appear. At this pressure the number of photons per laser shot was 104 which is sufficient for measuring the single shot XUV spectrum in the range 34 to 45 eV. The spectral profile was a super-continuum for some shots and discrete high harmonics for other shots. It is believed that the shot to shot variation of the spectra is due to the changes of the carrier envelope phase of the few-cycle laser pulses used for the polarization gating. An improved CE phase stabilization system in KLS further eliminated the statistical noise in our observation by allowing us to integrate data over several laser cycles for each CE phase value. The effect of CE phase on a polarization gated XUV spectrum was tested by changing the CE phase with two different methods. In the first method, the CE phase was changed by changing the thickness of fused silica plates on the beam path, and the result shows the shift in the spectral peak of the XUV when the gate width approached less than one optical cycle. As gate width was made less than half the optical cycle, the spectrum was observed with continuum harmonics separated by π radians. We believe that the presence of continuum and discrete harmonics spectra in the observation is due to single and double attosecond pulses generated in the polarization gating. In the second method the carrier-envelope phase of pulses from a grating-based chirped pulse amplification laser was varied smoothly to cover a 2π range by controlling the grating separation. The phase is measured simultaneously by an f-to-2f setup and by the variation of XUV spectra from polarization gated high harmonic generation. A very good similarity between the effect of single and double slits in Yong’s experiment and that of CE phase on the XUV spectrum in the polarization gating experiment has been found, giving better agreement with the theory. The effect of optical properties such as the Gouy phase shift on the polarization gated spectrum has also been studied in the course of investigating the best experimental optimizations to generate the most CE phase sensitive XUV spectrum with less statistical noise. This is the first time to our knowledge experimental study of the effect of the Gouy phase shift on a polarization gated XUV spectrum has been made.
Keywords: Harmonics generation; Polarization Gating; Super-continuum; Single Shot; Carrier Envelope Phase; X-ray streak camera; Deflection Dispersion; Soft X-ray; Physics, Atomic (0748); Physics, Molecular (0609); Physics, Optics (0752)